HPLC-DAD profiling and inhibitory potentials of ethylacetate and aqueous extracts of Talinum triangulare on key enzymes linked to type-2 diabetes (α-amylase and α-glucosidase) and oxidative stress (monoamine oxidase). Issue 1 (2nd January 2019) - Afolabi, Olakunle B.; Oloyede, Omotade I.; Agunbiade, Oludare S.; Obafemi, Tajudeen O.; Aline, B.; Obajuluwa, A.; Jaiyesimi, K.; Anadozie, S.
ABSTRACT: The current study explored various antioxidant properties and HPLC-DAD analysis of ethylacetate and aqueous extracts from Talinum triangulare ( T. triangulare ) as well as their inhibitory potentials on exzymatic activities implicated in type II diabetes. In this study, quantification of total antioxidant abilities revealed that ethylacetate and aqueous extracts of T.   triangulare had 11.52 ± 0.78 and 2.46 ± 0.26 mg (AAE/g), respectively. However, both extracts showed metal-chelating ability but aqueous extract had higher inhibition against Fe 2+ (IC50 = 0.50 ± 0.01 mg/ml) than ethylacetate extract (IC50 = 0.57 ± 0.01 mg/ml). There was no significant (p > 0.05) difference observed in their inhibitory activities against α-amylase activity, while ethylacetate extract had a strong inhibition (IC50 = 0.17 ± 0.01 mg/ml) on α-glucosidase activity than the aqueous extract (IC50 = 0.85 ± 0.01 mg/ml) in a concentration-dependent manner. Also, higher inhibition was noticed in ethylacetate extract against monoamine oxidase (IC50 = 99.72 ± 0.01 mg/ml) than the aqueous extract (IC50 = 141.08 ± 0.02 mg/ml). In addition, various polyphenolic contents were revealed via HPLC-DAD analysis in the extracts which could have engendered various inhibitions observed. Therefore, it could be suggested that, both extracts if properly annexed, could be promising alternative in the management of diabetes mellitus.